Characterization and evaluation of amine-modified graphene amphotericin B for the treatment of visceral leishmaniasis: in vivo and in vitro studies - Mudavath, Shyam Lal (Dove Medical Press, 2014)
Amphotericin B (AmB) has been the first-line treatment for visceral leishmaniasis (VL), a neglected protozoan disease, especially in regions like Bihar, India, where resistance to antimonials is widespread. However, adverse drug reactions are a major limiting factor. We evaluated a novel formulation of AmB conjugated to amine-modified graphene (f-Gr) for safety and efficacy over conventional AmB. The f-Gr was prepared in a gentle one-step process of noncovalent (amine) functionalization with the help of amino acid L-cysteine. This f-Gr was further conjugated to AmB by peptide bond. The conjugate (f-Gr-AmB) was characterized by Raman spectroscopy, Fourier transform infrared spectroscopy, scanning electron microscopy, and transmission electron microscopy. f-Gr-AmB was found to exhibit lesser cytotoxicity toward J774A.1 cells than AmB, and did not induce any hepatic or renal toxicity in Swiss albino mice. In vitro antileishmanial assay in J774A.1 cells showed significantly enhanced efficacy of f-Gr-AmB over AmB. Furthermore, percentage inhibition of amastigote replication in a hamster model of VL was significantly higher in the f-Gr-AmB treated group (87.8%) compared to the AmB group (70.4%). These results suggest that f-Gr-AmB could be a safe and effective alternative to conventional AmB in the treatment of VL.